The handbook of media audiences - Nightingale, Virginia; Wiley InterScience (Online service) (Chichester ; Malden, MA : Wiley-Blackwell, 2011)
"This handbook offers a comprehensive overview of the complexity and diversity of audience studies in the advent of digital media.-Recognizes and appreciates valuable traditional approaches and identifies how they can be applied to, and evolve with, the changing media world -Offers diverse perspectives from which being an audience, theorizing audiences, researching audiences, and doing audience research are approached today -Argues that the field works best by identifying particular 'audience problems' and applying the best theories and research methods available to solving them -Includes contributions from some of the most outstanding international scholars in the field"--
Introduction / Virginia Nightingale -- Part I. Being Audiences: 1. Readers as audiences / Wendy Griswold, Elizabeth Lenaghan, and Michelle Naffziger; 2. Listening for listeners : the work of arranging how listening will occur in cultures of recorded sound / Jackie Cook; 3. Viewing / Shawn Shimpach; 4. Search and social media / Virginia Nightingale; 5. Spreadable media : how audiences create value and meaning in a networked economy / Joshua Green and Henry Jenkins; 6. Going mobile / Gerard Goggin -- Part II. Theorizing Audiences: 7. Audiences and publics, media and public spheres / Richard Butsch; 8. The implied audience of communications policy making : regulating media in the interests of citizens and consumers / Sonia Livingstone and Peter Lunt; 9. New configurations of the audience? The challenges of user-generated content for audience theory and media participation / Nico Carpentier; 10. The necessary future of the audience ... and how to research it / Nick Couldry; 11. Reception / Cornel Sandvoss; 12. Affect theory and audience / Anna Gibbs -- Part III. Researching Audiences: 13. Toward a branded audience : on the dialectic between marketing and consumer agency / Adam Arvidsson; 14. Ratings and audience measurement / Philip M. Napoli; 15. Quantitative audience research : embracing the poor relation / David Deacon and Emily Keightley 16. Media effects in context / Brian O'Neill; 17. Cultivation analysis and media violence / Andy Ruddock; 18. Creative and visual methods in audience research / Fatimah Awan and David Gauntlett; 19. Locating media ethnography / Patrick D. Murphy -- Part IV. Doing Audience Research: 20. Children's media cultures in comparative perspective / Sonia Livingstone and Kirsten Drotner -- Fan cultures and fan communities / Kristina Busse and Jonathan Gray -- Beyond the presumption of identity? Ethnicities, cultures, and transnational audiences / Mirca Madianou; 21. Participatory vision : watching movies with Yolngu / Jennifer Deger; 22. The audience is the show / Annette Hill; 23. Seeking the audience for news : response, news talk, and everyday practices / S. Elizabeth Bird; 24. Sport and its audiences / David Rowe.
Includes bibliographical references and index.
Print version record.
Keywords: Mass media -- Audiences; Mass media and culture; SOCIAL SCIENCE -- Media Studies; Mass media and culture; Mass media -- Audiences